Deep learning for coders with fastai and PyTorch - Howard, Jeremy; Gugger, Sylvain (O'Reilly Media, Inc., 2020)
Deep learning has the reputation as an exclusive domain for math PhDs. Not so. With this book, programmers comfortable with Python will learn how to get started with deep learning right away. Using PyTorch and the fastai deep learning library, you'll learn how to train a model to accomplish a wide range of tasks-including computer vision, natural language processing, tabular data, and generative networks. At the same time, you'll dig progressively into deep learning theory so that by the end of the book you'll have a complete understanding of the math behind the library's functions.
Keywords: Machine learning; Apprentissage automatique